2013
DOI: 10.1039/c3ta12227a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced rate performance and cycling stability of a CoCO3–polypyrrole composite for lithium ion battery anodes

Abstract: A CoCO 3 -polypyrrole composite (CC-PPy) for lithium ion battery anodes was prepared by first synthesizing urchin-like CoCO 3 microspheres (CC) via a hydrothermal route and further modifying them with a PPy coating. The resulting CC-PPy exhibits excellent cycling stability, outstanding rate performance and a great recovery capability compared to CC, delivering a reversible capacity of 1070.7, 811.2, 737.6, 518.7, 504.5 and 559 mA h g À1 after 100 cycles at 0.1, 1, 2, 3, 4 and 5 C, respectively, and a recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
107
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 38 publications
4
107
0
Order By: Relevance
“…It has been proved that the practical capacities of some MCO 3 products are as high as or even higher than the corresponding transition metal oxides (MO) [7,9,10,18,20]. For example, the 10th reversible capacity of microspindle-like CoCO 3 could reach 1065 mAh g À1 , higher than that of microspindle-shaped CoO (~720 mAh g À1 ) operated at a same rate of 50 mA g À1 [18].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been proved that the practical capacities of some MCO 3 products are as high as or even higher than the corresponding transition metal oxides (MO) [7,9,10,18,20]. For example, the 10th reversible capacity of microspindle-like CoCO 3 could reach 1065 mAh g À1 , higher than that of microspindle-shaped CoO (~720 mAh g À1 ) operated at a same rate of 50 mA g À1 [18].…”
Section: Introductionmentioning
confidence: 96%
“…microcube, microsphere) mainly express unsatisfactory lithium storage capabilities due to their bad electronic conductivities or structural stabilities. Thus, conductive additives such as carbon nanotube (CN), conductive polymer and graphene are widely incorporated to improve the electronic conductivity of MCO 3 [9,10,13,30,31]. The resulted composites of MnCO 3 /CNs, CoCO 3 /polypyrrole and CoCO 3 /graphene exhibited a satisfactory retention capacity of~647 (100th, 100 mA g À1 ), 1070 (100th, 100 mA g À1 ) and 930 mAh g À1 (40th, 50 mA g À1 ), respectively [9,10,13].…”
Section: Introductionmentioning
confidence: 96%
“…The core level peak of Co 2p at 781.7 eV in Fig. 3a corresponds to the Co 2p 3/2 of CoCO 3 [24,29], which shifted to 780.7 eV in Zn 0.12 Co 0.88 CO 3 sample. It also should be noted that the peak at 785.6 eV (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Ding et al found that CoCO 3 ePPy composite exhibits significantly enhanced cycling stability compared to pure CoCO 3 , as well as excellent rate performance and a great recovery capability, which mainly resulting from the tightly packed PPy layer. It acts as not only a good electronic conductor, but also a flexible cushion, which effectively accommodates the volume change during the repeated cycling and avoids the disintegration of the electrode [24].…”
Section: Introductionmentioning
confidence: 99%
“…under the catalysis of newly generated metallic nanoparticles [18]. This mechanism had been further proved by studying the phase evolution of CC-PPy (CoCO 3 -polypyrrole) electrode during charge-discharge process using infrared spectrometry spectroscopy [19].…”
Section: Introductionmentioning
confidence: 98%